Negative pressure wound therapy with intermittent irrigation for treatment of post-traumatic giant abscess: A case report. (May 2022) - Abidali, Mohammad; Bauer, Frank; Gottlieb, Marc; Abidali, Ali
Abstract: Introduction: Negative pressure wound therapy (NPWT), also called vacuum-assisted closure, is an adjunctive therapy used to manage open wounds that apply subatmospheric pressure to the wound surface. The therapeutic effects of NPWT are exerted by stabilizing the wound environment, increasing blood flow, and macro-deformation of wounds that initiate granulation tissue formation. Case presentation: We present a case of a 28-year-old Caucasian male who developed a giant non-resolving hepatic abscess secondary to a gunshot wound (GSW) to the upper right abdomen. The abscess was successfully treated with open debridement followed by NWPT with instillation therapy. Significant reduction in abscess diameter and cessation of trauma-induced bile leak was observed following 15 days of wound vac treatment. Discussion: Wound vac treatment was essential in this patient due to the inherent erosive properties of bile that damage surrounding tissue and perpetuate opportunistic growth of pathogenic microbes. Prior to standard NPWT treatment, debridement of devitalized tissues and infection should be managed; however, instillation therapy has permitted NPWT to be used in the presence of infection or as an adjuvant to surgical infection management. Conclusion: NPWT is indicated for a wide range of acute and chronic wounds; however, the utilization of NPWT to treat abscesses remains unclear. Highlights: This case exhibits the novel use of NPWT to treat a hepatic abscess with bile leak. Instill wound VAC can reduce the bacterial wound burden and enhance wound healing. Hepatic abscess after trauma is a life-threatening condition with high morbidity. Operative management may be necessary for large non-resolving hepatic abscesses.